2018
DOI: 10.1136/thoraxjnl-2017-210670
|View full text |Cite
|
Sign up to set email alerts
|

Effective silencing of ENaC by siRNA delivered with epithelial-targeted nanocomplexes in human cystic fibrosis cells and in mouse lung

Abstract: IntroductionLoss of the cystic fibrosis transmembrane conductance regulator in cystic fibrosis (CF) leads to hyperabsorption of sodium and fluid from the airway due to upregulation of the epithelial sodium channel (ENaC). Thickened mucus and depleted airway surface liquid (ASL) then lead to impaired mucociliary clearance. ENaC regulation is thus a promising target for CF therapy. Our aim was to develop siRNA nanocomplexes that mediate effective silencing of airway epithelial ENaC in vitro and in vivo with func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…Therefore, ENaC represents an important therapeutic target. Its inhibition with small molecules or other therapeutic agents could bring a beneficial effect to all CF patients, irrespective of their mutations, and possibly to patients with other respiratory diseases (Caci et al., ; Coote et al., ; Hirsh et al., ; Scott et al., ; Shei, Peabody, Kaza, & Rowe, ; Tagalakis et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ENaC represents an important therapeutic target. Its inhibition with small molecules or other therapeutic agents could bring a beneficial effect to all CF patients, irrespective of their mutations, and possibly to patients with other respiratory diseases (Caci et al., ; Coote et al., ; Hirsh et al., ; Scott et al., ; Shei, Peabody, Kaza, & Rowe, ; Tagalakis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…ENaC is considered to be a key protein in the pathogenesis of the (Caci et al, 2009;Coote et al, 2015;Hirsh et al, 2008;Scott et al, 2017;Shei, Peabody, Kaza, & Rowe, 2018;Tagalakis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we used nanoparticles as a carrier system to deliver the ITCH siRNA in vivo. This was based on our previous findings that the receptor-targeted liposome-peptide-siRNA nanoparticle is an efficient delivery system for ex vivo and in vivo applications [49][50][51][52][53] . The formulation of the nanoparticles contains peptide ME27 which can mediate receptor-specific targeting via its interaction with integrin αvβ3 and αvβ5 on cells.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with nanoparticles in vitro. Nanoparticles were formulated as a mixture of Lipid:peptide:siRNA, as described previously 52,57 . In this study, we pre-formulated 3 different liposomes with different concentrations of PEG; 1) DOTMA/DOPE (DD), containing no PEG; 2) AT-1, DD containing 1% PEG; and 3) GK27, DD which contained 5% PEG.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed the promising chance to use this approach as co-adjuvant therapy for CF. Tagalakis et al (2018) developed siRNA nanocomplexes that could mediate silencing of airway epithelial sodium channel (ENaC) with functional correction of epithelial ion transport. Receptor-targeted nanocomplexes (RTNs) are made of cationic liposomes and targeting peptide mixed with siRNA.…”
Section: Liposomesmentioning
confidence: 99%